Randomized Clinical Trials in Stroke Research. (1st February 2010) - Ahn, Chul; Ahn, Daniel
Abstract : A randomized clinical trial is widely regarded as the most rigorous study design to determine the efficacy of intervention because spurious causality and bias associated with other experimental designs can be avoided. The purpose of this article is to provide clinicians and clinical researchers the types of randomized clinical trials used in stroke studies and to discuss the advantages and the limitations for each type of randomized stroke clinical trials.